Trastornos psicológicos y de calidad de vida en pacientes de cáncer de pulmón - Murillo, Mauricio; Pedraza, Juan D. (Psicooncología, 2006)
Psychosocial issues are a natural component of a cancer patient. The word cancer by itself brings a high level of uncertainty and fear, which generates high demands for the patient and his family. It has been established that 30-50% of patients with a cancer diagnosis have a significant degree of distress that requires treatment by professional staff. Approximately 174,470 newly diagnosed Lung cancer cases, and 164,460 deaths cause by this disease are expected in the year 2006. Lung cancer is one of the most common causes of cancer in the industrialized world. Lung cancer patients commonly experienced symptoms of distress and decrease in physical functioning related to the treatment and the disease itself. The impact of this phenomenon can be reflected in their emotional well being and their quality of life. Depression and Anxiety are the most frequent disorders present in these patients, unfortunately, very often, they are ignored and not treated. Patients that have difficulties adjusting to their new situation clearly represent a challenge to the treatment team. This article reviews the general psychosocial aspects of then lung cancer patient including aspects such as: symptoms distress, family distress, guilt and tobacco, quality of life and survivorship.